THE SIGNIFICANCE OF PRESERVING THE GENIUS LOCI IN NURTURING HISTORIC-RELIGIOUS URBAN SETTLEMENT CASE STUDY : KAMPUNG LUAR BATANG ( JAKARTA, INDONESIA) - Popi Puspitasari; Achmad Djunaedi; S Sudaryono; Heddy Shri Ahimsa Putra (TATALOKA, 2011)
Historic-Religious Kampung refers to the historical urban kampung which has an artifact or tradition of religious ritual. This type of kam-pong is able to grow independently because of the spirit that comes from its religious tradition, which in turn generating the resident’s and migrant’s economic activities. Currently there is an argument that formalism and universalism of the physical forms and the demolition of urban kampung have alienated the local spirit and culture. The socio-spatial-economic approach on to the historic-religious kampung case presented here will be significantly contributing to the preservation of the local spirit (Genius Loci). This paper is based on the empirical study of historic-religious kampung Luar Batang (Jakarta, Indonesia) which hopefully will be able to uncover the relationships between the local spirit and spatial structure. Dialogues based on the comparative study with the other similar kampung have been carried out as an attempt to conceptually formulate the significant aspects that would be useful for consideration in environmental regulation planning and maturation process, especially for the historic-religious kampung settlements in urban areas in Indonesia and other similar contexts.